2022
DOI: 10.3389/fvets.2022.938706
|View full text |Cite
|
Sign up to set email alerts
|

Owner assessed outcomes following elbow arthroscopy with or without platelet rich plasma for fragmented medial coronoid process

Abstract: ObjectiveDocument the outcomes of bilateral arthroscopic subtotal coronoidectomy for the fragmented medial coronoid process, quantify persistent lameness that required additional treatment (PRP), and document the outcomes of dogs that followed up with PRP injections.Study designRetrospective study.Sample populationOverall, 115 dogs underwent arthroscopy alone and 31 received PRP at least 6 weeks after arthroscopy. The owner's response rate was ~50% (73 dogs).MethodsCollected data included signalment, unilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
2
1
Order By: Relevance
“…[24][25][26] A recent study by Matos Cruz and Mason in dogs with medial coronoid disease that underwent bilateral arthroscopic subtotal coronoidectomy followed by PRP injection found that older dogs had less favourable outcomes. 27 In their study, the average age was 26.1 months, which was considerably older than in our study. An age effect is unlikely in this study as both groups were similar in age and could be classified as young.…”
Section: Discussioncontrasting
confidence: 62%
“…[24][25][26] A recent study by Matos Cruz and Mason in dogs with medial coronoid disease that underwent bilateral arthroscopic subtotal coronoidectomy followed by PRP injection found that older dogs had less favourable outcomes. 27 In their study, the average age was 26.1 months, which was considerably older than in our study. An age effect is unlikely in this study as both groups were similar in age and could be classified as young.…”
Section: Discussioncontrasting
confidence: 62%
“…20 In contrast, we used LOAD to assess function only at medium to long-term as well at final follow-up, similar to other studies. [43][44][45] LOAD questionnaire data was not collected at first presentation as all dogs showed severe lameness.…”
Section: Discussionmentioning
confidence: 99%
“…The LOAD questionnaire was developed to compare dogs prior to and after a certain treatment, for example whether or not a certain anti‐inflammatory improves signs of arthritis 20 . In contrast, we used LOAD to assess function only at medium to long‐term as well at final follow‐up, similar to other studies 43–45 . LOAD questionnaire data was not collected at first presentation as all dogs showed severe lameness.…”
Section: Discussionmentioning
confidence: 99%